A multi-sensor satellite assessment of SO2 emissions from the 2012-13 eruption of Plosky Tolbachik volcano, Kamchatka - Telling, J.; Flower, V. J. B.; Carn, Simon (Journal of Volcanology and Geothermal Research, 2015)
Prolonged basaltic effusive eruptions at high latitudes can have significant atmospheric and environmental impacts, but can be challenging to observe in winter conditions. Here, we use multi-sensor satellite data to assess sulfur dioxide (SO2) emissions from the 2012-2013 eruption of Plosky Tolbachik volcano (Kamchatka), which lasted ~9-10months and erupted ~0.55km3 DRE. Observations from the Ozone Monitoring Instrument (OMI), the Ozone Mapping and Profiler Suite (OMPS), the Atmospheric Infrared Sounder (AIRS), and the Moderate Resolution Imaging Spectroradiometer (MODIS) are used to evaluate volcanic activity, SO2 emissions and heat flux associated with the effusion of lava flows. Gaps in the primary OMI SO2 time-series dataset occurred due to instrument limitations and adverse meteorological conditions. Four methods were tested to assess how efficiently they could fill these data gaps and improve estimates of total SO2 emissions. When available, using data from other SO2 observing instruments was the most comprehensive way to address these data gaps. Satellite measurements yield a total SO2 loading of ~200kt SO2 during the 10-month Plosky Tolbachik eruption, although actual SO2 emissions may have been greater. Based on the satellite SO2 measurements, the Fast Fourier Transform (FFT) multi-taper method (MTM) was used to analyze cyclical behavior in the complete data series and a 55-day cycle potentially attributable to the eruptive behavior of Plosky Tolbachik during the 2012 - 2013 eruption was identified.